2004
DOI: 10.1097/01.aud.0000120362.69077.0b
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Z-Score–Based Method to Analyze Candidate Genes for Age-Related Hearing Impairment

Abstract: The Z-score conversion appears to be a valid method to describe to what extent a subject is affected by ARHI, allowing to compare persons from different age and gender. This method can be the basis of future, powerful studies to identify ARHI genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Frequency-specific thresholds were converted to sex-and ageindependent Z-scores based on the ISO 7029 standards [International Organisation for Standardisation, 2000;Fransen et al, 2004]. The Z-score is defined as the number of standard deviations the hearing threshold differs from the median value at a specific frequency.…”
Section: Materials and Methods Calculating Z-scoresmentioning
confidence: 99%
“…Frequency-specific thresholds were converted to sex-and ageindependent Z-scores based on the ISO 7029 standards [International Organisation for Standardisation, 2000;Fransen et al, 2004]. The Z-score is defined as the number of standard deviations the hearing threshold differs from the median value at a specific frequency.…”
Section: Materials and Methods Calculating Z-scoresmentioning
confidence: 99%
“…Van Laer et al [70] reported two independent association studies, using two non-synomous SNPs within the DFNA5 gene, to investigate its possible involvement in ARHL, but no allelic or genotypic association was detected. In another study, Fransen et al [71] define a quantitative trait (QT) value, correcting for age and gender, to allow the genetic study of ARHL as a QT. No association was found; however, this approach may improve the power to detect genes with small to medium effects and circumvents the difficulty of assigning case and control status to what is a continuous trait.…”
Section: Association Studiesmentioning
confidence: 99%
“…A disadvantage of treating ARHI as a dichotomous trait (affected/unaffected) is the loss of statistical power, as generally information is lost when a quantitative trait such as ARHI is dichotomized [Page and Amos, 1999]. Fransen et al [2004] proposed the calculation of a Zscore to enable treatment of ARHI as a quantitative trait. This Z-score is an age-and gender-independent value, based upon the ISO 7029 standard [Fransen et al, 2004].…”
Section: How To Analyze Genetic Factors Involved In Human Arhimentioning
confidence: 99%
“…Fransen et al [2004] proposed the calculation of a Zscore to enable treatment of ARHI as a quantitative trait. This Z-score is an age-and gender-independent value, based upon the ISO 7029 standard [Fransen et al, 2004]. Using this approach, random samples genotyped for a particular SNP in a candidate gene can be grouped according to their genotype and subsequently statistically analyzed using ANOVA-based methods.…”
Section: How To Analyze Genetic Factors Involved In Human Arhimentioning
confidence: 99%